Simultaneous switching noise analysis using application specific device modeling. - Li Ding
In this paper, we introduce an application-specific device modeling methodology to develop simple device model that accurately tracks the actual device I-V characteristics in relevant but bounded operating regions. We have specifically used a simple MOSFET model to precisely analyze the switching noises generated on a chip due to simultaneous driving of chip output pads by bulky buffer gates. Previous works in analytical modeling of simultaneous switching noises employed long-channel and α-power law transistor models; however, these models led to complex circuit equations that on truncation caused poor matching between manual analysis and actual simulation results. Also, in order to retain the simplicity of manual analysis, previous researchers ignored the parasitic capacitances of the bonding pads. This paper demonstrates that by using a simple application-specific transistor model, circuit equations can be solved precisely without requiring any gross approximations or model truncations, even when the inductance effects of bonding wires are simultaneously considered along with parasitic capacitances of the output pads. The analytical results derived in this paper tally with HSPICE simulation values within 3% deviations.
Keywords: MOSFET; Analytical modeling; Parasitic capacitance; Specific device modeling; Switching noise analysis; Transistor models